(3GdYfhGf aj GNJdGa GdbQGA GdSHYIs - (3ESeGYjd Hf Nda GdfMhj GdebQj, CHh WGgQ,J (B455 (3g` s
(3ChdgG (B:s
(3CeG HYO aEfj PGcQ aj gPG GdcJGH Ef TGA Gddg eG GNJda ajg GdbQGA GdSHYI GdeTghQhf ef CFeI GdCeUGQ HELGR hGNJUGQ s
(3BNQgG (B:s
(3hbO GNJda Yfg aj ShQI daX GdJcHjQ hGdPj GNJGQg ef Pdc Gddg Je GdcJGH GdoeSei HGdYfhGf aj GdbQGAGJ GdSHY s
(3GdfSNI HgG MhGTs
(3fSNI QGHYIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1176s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
Keywords: (3GdbQGAGJ hGdJLhjOs